2014
DOI: 10.2174/1874079001407010011
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Health Care Professionals in Providing Smoking Cessation Advice in Najran Armed Forces Hospital, KSA

Abstract: Background: Smoking is an established risk factor for many diseases and is one of the most important public health problems worldwide. According to the WHO, medical and paramedical staff can influence positively or negatively the smoking habits of a community. Objective: To explore the predictors of providing smoking cessation advice by medical and paramedical staff. Methods: We have conducted a cross-sectional study from April, 2014 through May, 2014 in Najran Armed Forces Hospital. Data collection was done u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Furthermore, this study showed that 86.5% of smokers had very high positive attitudes towards establishing smoking cessation clinics. This is also high compared to that reported in other studies 10,11 . Such results indicate a strong tendency by HCWs to quit smoking and highlight their need for external support.…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…Furthermore, this study showed that 86.5% of smokers had very high positive attitudes towards establishing smoking cessation clinics. This is also high compared to that reported in other studies 10,11 . Such results indicate a strong tendency by HCWs to quit smoking and highlight their need for external support.…”
Section: Discussionmentioning
confidence: 37%
“…In the south-western region of the country, the overall prevalence of tobacco use was 26.3% 10 . A recent cross-sectional study conducted in Najran Armed Forces Hospital concluded that the overall prevalence of tobacco use among medical and paramedical staff was 21.1% 11 . Another study done in the eastern region revealed that 15.1% of healthcare providers were smokers 12 .…”
Section: Introductionmentioning
confidence: 99%
“…As the largest group of healthcare professionals, estimated at 19 million worldwide (over 90,000 in Czech Republic, 250,000 in Poland), nurses are uniquely positioned to offer cessation interventions to patients (WHO, ). Nurses’ cessation interventions are effective, and hospitalization offers a good opportunity for smokers to consider quitting (Fiore et al., ; Harrabi, al Harbi, & al Ghamdi, ; Rice, Hartmann‐Boyce, & Stead, ). Nurses are well positioned to deliver tobacco dependence treatment, as nurses’ contact with patients and families throughout hospitalization offer a range of opportunities for this intervention.…”
Section: Background and Significancementioning
confidence: 99%